2021
DOI: 10.30939/ijastech..928581
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of The Effect of Solid Lubricant Particle Sizes on Friction and Wear Properties in Friction Composites: An Experimental Case Study with Graphite

Abstract: Friction composites consist of many materials with various properties. Solid lubricant is one of these materials. The task of the solid lubricant in the compo-site is to protect the counter surfaces against wear and to reduce noise and vibra-tion. Typical solid lubricants used in the friction composite are graphite, antimo-ny trisulfide, molybdenum disulfide, copper sulfide, etc. The selection suitable solid lubricants for better braking performance is an important issue, as solid lubricants may decompose at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For this reason, many attempts have been made to improve friction properties by controlling the composition and content of lubricants (John and Menezes, 2021). In industry, FeS 2 is frequently used (Sugözü and Sugözü, 2021; Makoto Miyajima et al 2016). The component is very cheap, easy to obtain and has lubricating properties when used properly in friction material manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many attempts have been made to improve friction properties by controlling the composition and content of lubricants (John and Menezes, 2021). In industry, FeS 2 is frequently used (Sugözü and Sugözü, 2021; Makoto Miyajima et al 2016). The component is very cheap, easy to obtain and has lubricating properties when used properly in friction material manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Fillers are used to reduce costs and increase thermal stability (Öktem and Uygur, 2019). Researchers frequently use barite as a filler material due to its positive effect on brake friction materials (Singh, 2021a; Sugözü and Sugözü, 2021). Researchers have reported that different fillers other than barite also increase friction performance.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their lamellar structure, which assists in the formation of a robust friction/transfer layer on the mating surfaces with strong adhesion [19][20][21][22]. The metal sulfides can either be used individually or can be added in a mix in the composition [23]. Graphite is primarily known for its good lubrication characteristics, high thermal conductivity, reduction in excessive wear of contact surfaces by contributing towards the formation of the friction/tribo-layer, high damping, and superior seizure resistance [6,24].…”
Section: Introductionmentioning
confidence: 99%